In-hospital resource utilization in surgical and transcatheter aortic valve replacement - Reinöhl, Jochen (BMC Cardiovasc Disord, 2015)
BACKGROUND: Little is known about preoperative predictors of resource utilization in the treatment of high-risk patients with severe symptomatic aortic valve stenosis. We report results from the prospective, medical-economic “TAVI Calculation of Costs Trial”. METHODS: In-hospital resource utilization was evaluated in 110 elderly patients (age ≥ 75 years) treated either with transfemoral (TF) or transapical (TA) transcatheter aortic valve implantation (TAVI, N = 83), or surgical aortic valve replacement (AVR, N = 27). Overall, 22 patient-specific baseline parameters were tested for within-group prediction of resource use. RESULTS: Baseline characteristics differed between groups and reflected the non-randomized, real-world allocation of treatment options. Overall procedural times were shortest for TAVI, intensive care unit (ICU) length of stay (LoS) was lowest for AVR. Length of total hospitalization since procedure (THsP) was lowest for TF-TAVI; 13.4 ± 11.4 days as compared to 15.7 ± 10.5 and 21.2 ± 15.4 days for AVR and TA-TAVI, respectively. For TAVI and AVR, EuroScore I remained the main predictor for prolonged THsP (p <0.01). Within the TAVI group, multivariate regression analyses showed that TA-TAVI was associated with a substantial increase in THsP (55 to 61 %, p <0.01). Additionally, preoperative aortic valve area (AVA) was identified as an independent predictor of prolonged THsP in TAVI patients, irrespective of risk scores (p <0.05). CONCLUSIONS: Our results demonstrate significant heterogeneity in patients baseline characteristics dependent on treatment and corresponding differences in resource utilization. Prolonged ThsP is not only predicted by risk scores but also by baseline AVA, which might be useful in stratifying TAVI patients. TRIAL REGISTRATION: German Clinical Trial Register Nr. DRKS00000797